High-density array-CGH with targeted NGS unmask multiple noncontiguous minute deletions on chromosome 3p21 in mesothelioma - Yoshikawa, Yoshie; Emi, Mitsuru; Hashimoto-Tamaoki, Tomoko; Ohmuraya, Masaki; Sato, Ayuko; Tsujimura, Tohru; Hasegawa, Seiki; Nakano, Takashi; Nasu, Masaki; Pastorino, Sandra; Szymiczek, Agata; Bononi, Angela; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
We used a custom-made comparative genomic hybridization array (aCGH; average probe interval 254 bp) to screen 33 malignant mesothelioma (MM) biopsies for somatic copy number loss throughout the 3p21 region (10.7 Mb) that harbors 251 genes, including BRCA1 (breast cancer 1)-associated protein 1 (BAP1), the most commonly mutated gene in MM. We identified frequent minute biallelic deletions (<3 kb) in 46 of 251 genes: four were cancer-associated genes: SETD2 (SET domain-containing protein 2) (7 of 33), BAP1 (8 of 33), PBRM1 (polybromo 1) (3 of 33), and SMARCC1 (switch/sucrose nonfermentable- SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily c, member 1) (2 of 33). These four genes were further investigated by targeted next-generation sequencing (tNGS), which revealed sequence-level mutations causing biallelic inactivation. Combined high-density aCGH and tNGS revealed biallelic gene inactivation in SETD2 (9 of 33, 27%), BAP1 (16 of 33, 48%), PBRM1 (5 of 33, 15%), and SMARCC1 (2 of 33, 6%). The incidence of genetic alterations detected is much higher than reported in the literature because minute deletions are not detected by NGS or commercial aCGH. Many of these minute deletions were not contiguous, but rather alternated with segments showing oscillating copy number changes along the 3p21 region. In summary, we found that in MM: (i) multiple minute simultaneous biallelic deletions are frequent in chromosome 3p21, where they occur as distinct events involving multiple genes; (ii) in addition to BAP1, mutations of SETD2, PBRM1, and SMARCC1 are frequent in MM; and (iii) our results suggest that high-density aCGH combined with tNGS provides a more precise estimate of the frequency and types of genes inactivated in human cancer than approaches based exclusively on NGS strategy.